Forecasting Livestock and Poultry Production in India - Arya S. Nair; M.Thirunavukkarasu; A.Serma Saravana Pandian; G.Senthilkumar; C.Balan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The challenges faced by India in achieving the food and nutritional security to the fast growing population need a concerted approach for growth of livestock sector. Various forecasting models like combinations of ARIMA models and Exponential Smoothing models like Simple, Holt, Brown and Damped trend were used to identify the growth patterns and to predict the future trends in livestock and poultry production in India. Time series data on milk production from 1950-51 to 2017-18 were used to forecast the milk production in India up to 2050-51. Brown Exponential Smoothing was the best fit model for forecasting of milk production in India. The forecast obtained showed that milk production would increase to 207.57, 311.86, 416.16 and 520.45 MT respectively during 2020-21, 2030-31, 2040-41 and 2050-51 from 121.80 MT during the year 2010-11. ARIMA (0,1,1) was the best fit model for forecasting meat and wool production, the forecasted values of meat production showed that meat production would increase from 1.08 MT in 2000-01 to 5.18, 7.63, 10.07 and 12.52 MT, respectively during 2020-21, 2030-31, 2040-41 and 2050-51. Wool production would increase appreciably over years with a production of 46.26, 52.06, 58.59 and 65.17 million kg, respectively during the years 2020-21, 2030-31, 2040-41 and 2050-51 from 43.00 million kg in 2010-11. The Brown Exponential Smoothing model was the best fit model for forecasting egg production in India. The forecasted values obtained from the best fitted Brown ES was 103341.99, 144374.02, 185406.04 and 222334.86 million numbers during the years 2020-21, 2030-31, 2040-41 and 2050-51, respectively.